Principles of highway engineering and traffic analysis - Mannering, Fred L.; Washburn, Scott S. (Hoboken, NJ : Wiley, 2013)
"The 5th edition of the Mannering's Principles of Highway Engineering and Traffic Analysis continues to offer a concise approach that covers all the necessary fundamental concepts. New features in this edition include updates and more consistency with the latest edition of the Highway Capacity Manual (HCM); the inclusion of sample FE exam questions, call-out of common mistakes; and added coverage on a qualitative description of the mechanistic approach"--
Includes index.
0
Keywords: Highway engineering; Traffic engineering; TECHNOLOGY & ENGINEERING / Civil / General